New color patterns and new synonym of Odontolabis sinensis (Westwood, 1848) (Coleoptera: Lucanidae): insights from a multilocus phylogeny and species delimitation - Ying, Ying; Zhan, Zhi-Hong; Wan, Xia (Zootaxa, 2021)
Taxonomy of Odontolabis sinensis (Westwood, 1848) and Odontolabis fallaciosa Boileau, 1901 has long been a controversial issue due to their highly morphological similarity except for elytral color patterns. In the present work, we assessed their taxonomic status by combining molecular phylogeny and species delimitation based on multilocus datasets (COI, 16S rDNA, Cytb, CAD, Wingless). Phylogenetic analyses under both Maximum Likelihood inference and Bayesian inference recovered identical topologies. All the examined individuals in the clade of O. sinensis and O. fallaciosa formed into five subclades belonging to four color patterns, respectively. The Kimura-2-Parameter (K2P) genetic distance analysis yielded a low mean value (0.0108−0.0295). The multiple species delimitations (ABGD, PTP and GMYC) reinforced them to be one MOTU. Our results suggest that these clades belong to the same species, and thus we propose O. fallaciosa to be a junior subjective synonym of O. sinensis. We also found two new color patterns corresponding to two clades from Southwestern China (north of 20°N and east of 105°E), respectively displaying the reddish-orange, slenderly rimmed patch and brownish-orange broad patches along the elytral edge, which was probably attributable to both historical and ecological factors in this particular region.